PRODUKTIVITAS DAN EKONOMI KELUARGA TENAGA KERJA PEREMPUAN PADA UKM KONVEKSI DI KABUPATEN KUDUS (STUDI KASUS DI KECAMATAN KOTA KABUPATEN KUDUS) - Rodhiyah Rodhiyah (Faculty of Social and Political Sciences, Universitas Diponegoro, 2014)
Female labors shows contribution in economic activity, for example in SMEs case: convection, provides many opportunities for the female workers, because they can use their the skills in it. On the other hand in the household, the husband as the head of the household income is insufficient for the needs of the family . Women's participation in economic activity is expected, to contribute to the family economy, to achieve that it is required a fairly high level of productivity, but in fact, the result is not maximum. The purpose of research is to discover economic conditions of the female labor and women labor productivity, identify factors driving and inhibiting female labor productivity, contribution of the female labor economics family. The purpose of research is to discover economic conditions of the female labor and women labor productivity, identify factors driving and inhibiting female labor productivity, contribution of the female labor economics family.In this paper cross sectional is used as the research method, descriptive analytic sample of 100 women workers in four SMEs convection located in Kudus City District is selected using “purposive” and “accidental” methods, then the data is analyzed “descriptively” with frequency tables,then the results are presented as narrative. Results and analysis In this paper cross sectional is used as the research method, descriptive analytic sample of 100 women workers in four SMEs convection located in Kudus City District is selected using “purposive” and “accidental” methods, then the data is analyzed “descriptively” with frequency tables, then the results are presented as narrative. Results and analysis The working income based on the target, but the female labor do not feel it as a heavy burden. The product results are consistent to the quality threshold, none were ever a damaged product, the female labor complete the work appropriate with the deadline. Supporting productivity factor: skill , experience, responsibility, discipline(rarely late, rarely absent), efficiently using their break time: taking a break while completing the unfinished work . Inhibiting productivity factor: often too late, frequently absent to complete homework as a housewife, SME does not have strict rules. The income is dynamic, no fix income, i.e.: daily, based batches, sometimes really low. Although most of them feel sufficient with the salary, but there are labors who feels their salary is not enough for daily rules. Therefore, they work harder to solve this problem, or they try to reduce their expenditure.